Features of phytogenic relief formation in the floodplain of the Oster river - Філоненко, Ю. М. (Київський національний університет імені Тараса Шевченка, 2021)
During 2015-2020, we conducted field studies of phytogenic relief in the Oster river floodplain. In the process, the method of field route observations, polls, photography, morphological and mophometric analyses were actively used. Mathematical methods and computer technologies were used to process and summarize the obtained data. Based on the processing of literary and cartographic sources, Internet sources and field research data, it is established that the natural conditions and vegetation features of the Oster river floodplain are favourable for the emergence of numerous relief forms of phytogenic origin. During field and in-house research we studied the causes and identified the peculiarities of appearance of the most common here accumulative and denudation phytogenic landforms. In particular, we analyzed tussocks and their clusters on the surface of swamps and wetlands; humps formed by large trees with roots blown over by the wind (“earth walls”) and microchains formed by tree trunks, trunk humps and trunk depressions; soil mounds, holes formed by large trees with roots blown over by the wind as well as passages of roots and rhizomes. It is found that the accumulative relief forms of phytogenic origin in the floodplain of the Oster river significantly outnumber the denudation ones. In addition, in the Oster floodplain, as in most forests of Chernihiv region, the number of “earth walls” and holes formed by large trees with roots blown over by the wind significantly exceeds the number of chains. This is due to the fact that after strong winds the trunks of fallen trees in most cases are sawn and removed but the fallen root part remains. It is established that the term of existence of phytogenic forms of relief varies from several hundreds or tens of years to several years. Their highest density is observed within swamps, wetlands, forests and meadows. By size, phytogenic landforms mostly have the rank of nanorelief. Microforms of phytogenic relief are much less common. It is found that the phytogenic landforms of the investigated area undergo a significant transformation due to fires. Numerous depressions (“burns”) appear within the drained swamps and wetlands under the action of flames.

Аналіз даних польових досліджень, літературних і картографічних джерел, джерел з мережі Інтернет, дозволяє стверджувати, що природні умови та особливості рослинності території заплави річки Остер сприяють виникненню численних форм рельєфу фітогенного походження. Під час польових та камеральних досліджень нами вивчено причини і виявлено особливості виникнення найбільш поширених тут акумулятивних і денудаційних фітогенних форм рельєфу. Зокрема досліджено купини та їх скупченнями на поверхні боліт і заболочених ділянок; вітровальні горби і мікропасма, пристовбурові горби і міжстовбурові зниженнями; дернові горбочки, вітровальні ями, а також ходи коренів та ризоїдів. Охарактеризовано їх розміри та щільність розташування у межах окремих ділянок дослідженої території. Виявлено, що акумулятивні форми рельєфу фітогенного походження на території заплави річки Остер кількісно значно переважають денудаційні. Встановлено, що найбільша щільність фітогенних форм рельєфу спостерігається у межах боліт, заболочених ділянок, лісових масивів та луків і за розміром вони переважно мають ранг нанорельєфу. Виявлено, що фітогенні форми рельєфу дослідженої території зазнають суттєвої трансформації внаслідок впливу пожеж.
Особливості фітогенного рельєфоутворення в заплаві річки Остер
Keywords: фітогенний рельєф; вітровальний горб; купина; вітровальна яма; пристовбурове підняття; пасмо; болото; phytogenic relief; humps formed by large trees with roots blown over by the wind; tussock; holes formed by large trees with roots blown over by the wind; trunk hump; chain; swamp